Unveiling the formation 1 : 2 supramolecular complexes between cucurbit[7]uril and a cationic calix[4]arene derivative - Pessêgo, Márcia (2019)
This work was supported by the FCT (Portugal), MICINN (Spain) and ERDF through grants UID/QUI/50006/2019; UID/Multi/04326/2019; ALG-01-0145-FEDER-022121 PTDC/QUI-COL/32351/2017; CEECIND/00466/2017; CTQ2017284354-P; GR 2007/085; IN607C 2016/03 and ED431G/09.